The Influence of Servant Leadership on Job Performance Mediated by Job Satisfaction, Employee Engagement, and Organizational Citizenship Behavior Among Lecturers of Private Higher Education Institutions in West Java - Yus Jayusman; Bahtair Usman; Dita Oki Berliyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Objectives: This study aims to analyze the direct and indirect effects of Servant Leadership on lecturers’ Job Performance through the mediating variables of Job Satisfaction, Employee Engagement, and Organizational Citizenship Behavior (Organizational Citizenship Behavior). The study also seeks to identify which mediating variable has the strongest influence in explaining the relationship between leadership and performance among lecturers in private universities. Methodology: This study applies a causal quantitative approach using a survey method with a sample of 155 lecturers from Information Technology study programs at private universities in West Java. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test ten research hypotheses and evaluate the mediating effects among variables. Findings: The results show that Servant Leadership has a positive influence on Job Satisfaction, Employee Engagement, and Organizational Citizenship Behavior, but does not directly affect Job Performance. Among the mediators, only Organizational Citizenship Behavior significantly mediates the relationship between Servant Leadership and Job Performance, indicating that lecturers’ voluntary behavior plays a key role in improving performance. In contrast, Job Satisfaction and Employee Engagement do not act as significant mediators. Conclusion: The findings highlight that leadership effectiveness in higher education depends on fostering Organizational Citizenship Behavior rather than relying solely on satisfaction or engagement. The study introduces the concept of Emphatic Leadership, which emphasizes empathy, accountability, and humility as essential values for leaders in academic environments. This approach offers practical insights for developing participative and humanistic leadership models to enhance lecturers’ academic performance.